Music, Algorithms, and Popularity: How TikTok Trends Act as Catalysts in Shaping Contemporary Culture - Harold Marshall Simalango; Erika Amelia; Rintia Marsyanda; Duta Ananda; Muhammad Rendy Sanjaya Putra; Afrizal Yudha Setiawan; Chhorn Chanthy (Program Studi Pendidikan Musik FBS UNP, 2025)
Objective: This study aims to examine TikTok’s role as a catalyst in shaping music trends through its algorithms and popularity dynamics. Method: A content analysis was conducted on 35 TikTok audio and video clips that went viral in 2024-2025 to understand the relationship between music, algorithms, and digital popular culture. Results and Discussion: The findings reveal that the popularity of music on TikTok is not solely dependent on its artistic value but also on how users package the song within the context of digital culture, such as dance challenges, memes, and remixes. TikTok’s algorithm facilitates rapid music dissemination, leveraging social dynamics and advanced algorithmic strategies. Conclusion: TikTok functions not only as a music distribution platform but also as a cultural agent that shapes music preferences and accelerates the viral cycles of songs within the contemporary music industry. This study contributes to the field of music and digital media by highlighting how platform algorithms can shape cultural preferences and the broader dynamics of the music industry.